Tissue Engineering: Intra‐Operative Bioprinting of Hard, Soft, and Hard/Soft Composite Tissues for Craniomaxillofacial Reconstruction (Adv. Funct. Mater. 29/2021). (16th July 2021) - Moncal, Kazim K.; Gudapati, Hemanth; Godzik, Kevin P.; Heo, Dong N.; Kang, Youngnam; Rizk, Elias; Ravnic, Dino J.; Wee, Hwabok; Pepley, David F.; Ozbolat, Veli; Lewis, Gregory S.; Moore, Jason Z.; et al.
Abstract : In article number 2010858, Ibrahim T. Ozbolat and co‐workers demonstrate intra‐operative bioprinting for repairing stratified hard/soft composite tissues in situ, which enables complex tissue heterogeneity in an anatomically accurate manner. Intra‐operative bioprinting could be absolutely unique in the clinical realm of craniomaxillofacial defects and is expected to have a significant impact on the reconstructive algorithm for the current challenging clinical dilemmas.